Różny przebieg kliniczny rozsianego krzepnięcia wewnątrznaczyniowego (DIC) w okresie ustalania rozpoznania ostrej białaczki monoblastycznej (AML-M5) u 2 dzieci - Sikorska-Fic, Barbara; Niewiadomska, Edyta; Chyżyński, Bartosz; Matysiak, Michał (Pediatria Polska - Polish Journal of Paediatrics, 2017)
Disseminated intravascular coagulation (DIC) is usually observed in acute promielocytic leukemia (AML-M3). DIC is diagnosed in other types of acute myeloid leukemia less frequently, but among them, the largest percentage applies to patients with acute monoblastic leukemia (AML-M5), with the release of procoagulation substances and cytokines from blasts. Laboratory and clinical symptoms of DIC appeared at the time of diagnosis of leukemia or just after initiation of induction treatment. We present two children with AML-M5 and rearrangement of the MLL gene, treated according to BFM AML 98 Interimphase 2004 and BFM AML 2012 protocol. The first patient had laboratory signs of DIC as undetectable (below quantifiable levels of) coagulation parameters without any clinical symptoms diagnosed at the same time as leukemia and persistent during the induction chemotherapy. The second patient had changes first in the coagulogram on the second day of induction chemotherapy. In the subsequent days, major bleeding from mucous membranes of the oral cavity, requiring intensive substitute treatment, was observed. The highest concentration of D-dimers with the lowest concentration of fibrinogen was observed on day 5 of chemotherapy in both the cases. Coagulation parameters were within normal levels on the last day, e.g. on Day 8 of induction chemotherapy, despite intensive substitution therapy.